2021
DOI: 10.3389/fmicb.2021.629387
|View full text |Cite
|
Sign up to set email alerts
|

CgNPG1 as a Novel Pathogenic Gene of Colletotrichum gloeosporioides From Hevea brasiliensis in Mycelial Growth, Conidiation, and the Invasive Structures Development

Abstract: The rubber tree (Hevea brasiliensis) is a tropical perennial crop for the primary source of natural rubber. Colletotrichum gloeosporioides from Hevea brasiliensis (C. gloeosporioides Hb) and Colletotrichum acutatum from Hevea brasiliensis (C. acutatum Hb) are the causal agents of rubber tree anthracnose and lead to serious loss of natural rubber production. Inoculation tests showed that C. gloeosporioides Hb possessed higher pathogenicity than C. acutatum Hb to the rubber tree. Genomic analysis revealed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The radial growth, conidiation, and appressorium formation assays were performed as described by Liang et al ( 2021 ). For the vegetate growth assay, 5-mm-diameter mycelium disks were inoculated on potato dextrose agar medium and cultured for 6 days, the diameters of the colonies were recorded, and the growth rates were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radial growth, conidiation, and appressorium formation assays were performed as described by Liang et al ( 2021 ). For the vegetate growth assay, 5-mm-diameter mycelium disks were inoculated on potato dextrose agar medium and cultured for 6 days, the diameters of the colonies were recorded, and the growth rates were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Colletotrichum causes anthracnose on a wide variety of woody plants in tropical, subtropical, and temperate climates (Liang et al, 2021 ). In Colletotrichum , six NLP homologs were identified in the Colletotrichum higginsianum genome.…”
Section: Introductionmentioning
confidence: 99%
“…The generation and development of conidia requires direct expression of several key regulators for proper vegetative growth, the assembly of the conidiophore, and spore maturation. Recently, Liang et al (2021) found that the function of CgNpg1 (novel pathogenic gene 1) in C. gloeosporioides is essential for mycelial growth, conidiation, the development of invasive structures such as conidial germination, appressorium formation, and pathogenicity. CgChip6 encodes a novel fungal virulence factor, sterol glycosyl transferase, that is induced by hard surface contact of the conidia and is involved in conidial germination and appressorium formation (Kim et al, 2002).…”
Section: Identification and Pathogenicity Of Colletotrichum Spp In Te...mentioning
confidence: 99%
“…Colletotrichum causes anthracnose on a wide variety of woody plants in tropical, subtropical and temperate climates (Liang et al, 2021). C. gloeosporioides is the dominant causal agent of rubber tree anthracnose and leads to serious loss of natural rubber production (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%